A comprehensive bibliometric exploration of hydrogel applications in spinal cord injury - Han, Guosong; Zhang, Huihui; Li, Zhixiang (Frontiers in Pharmacology, 2025)
IntroductionSpinal cord injury (SCI) represents a severe traumatic disorder of the central nervous system, leading to potential loss of motor and sensory functions. Its intricate pathological mechanism renders its treatment a formidable challenge. Recently, hydrogels have emerged as promising materials for spinal cord repair due to their exceptional biocompatibility and biodegradability, garnering significant attention. Consequently, extensive research on hydrogel applications in spinal cord injuries aims to provide an in-depth understanding of this field’s current state and delineate future research trajectories.MethodsA thorough search was conducted using the Web of Science Core Collection (WoSCC). Bibliometric tools such as CiteSpace, VOSviewer, Scimago Graphica, R and Bibliometrix software were employed to construct a knowledge map regarding the application of hydrogel in SCI.ResultsA bibliometric analysis of 1,015 publications between 2000 and 2025 elucidates the current research landscape, developmental trends, academic impact, and emerging knowledge dissemination patterns in hydrogel applications for SCI. The international collaboration in hydrogels-based SCI research exhibits a China-U.S.-centered network structure: as the top two publishing countries (464 vs. 278 publications), they maintain the closest bilateral collaboration, collectively forming a prominent transnational research network. The journal Biomaterials boasts the highest number of publications with 58 articles. Among prolific authors, Shoichet, Molly S., has authored the most papers, totaling 38 articles. There is a notable collaboration among various countries and institutions, with current research predominantly focusing on inflammation, apoptosis, nanoparticles, and injectable hydrogels. These efforts aim to achieve functionalized hydrogel regulation of microenvironmental changes, emerging as a focal point in contemporary research. This research highlights the latest trend of hydrogels in the treatment of SCI, thus pointing out the direction for new treatment strategies.DiscussionThe current research focus, which include the integration of functionalized hydrogels with biological factors, are setting the stage for subsequent investigative endeavors and the eventual clinical application of hydrogel in the treatment of SCI. This comprehensive analysis not only delineates the current state and emerging frontiers of hydrogel-based treatments for SCI but also provides a roadmap for future innovation.